The detyrosination/re-tyrosination cycle of tubulin and its role and dysfunction in neurons and cardiomyocytes. (15th March 2023) - Sanyal, Chadni; Pietsch, Niels; Ramirez Rios, Sacnicte; Peris, Leticia; Carrier, Lucie; Moutin, Marie-Jo
Abstract: Among the variety of post-translational modifications to which microtubules are subjected, the detyrosination/re-tyrosination cycle is specific to tubulin. It is conserved by evolution and characterized by the enzymatic removal and re-addition of a gene-encoded tyrosine residue at the C-terminus of α-tubulin. Detyrosinated tubulin can be further converted to Δ2-tubulin by the removal of an additional C-terminal glutamate residue. Detyrosinated and Δ2-tubulin are carried by stable microtubules whereas tyrosinated microtubules are present on dynamic polymers. The cycle regulates trafficking of many cargo transporting molecular motors and is linked to the microtubule dynamics via regulation of microtubule interactions with specific cellular effectors such as kinesin-13. Here, we give an historical overview of the general features discovered for the cycle. We highlight the recent progress toward structure and functioning of the enzymes that keep the levels of tyrosinated and detyrosinated tubulin in cells, the long-known tubulin tyrosine ligase and the recently discovered vasohibin-SVBP complexes. We further describe how the cycle controls microtubule functions in healthy neurons and cardiomyocytes and how deregulations of the cycle are involved in dysfunctions of these highly differentiated cells, leading to neurodegeneration and heart failure in humans.